(untitled) (Journal of Pharmaceutical Negative Results, 2023)
We all are consumers and we use numerous products and services to satisfy our needs similarly Cosmetic products sales are at their peak in the contemporary times. There are numerous factors which have a direct or indirect impact on consumer buying behaviour. Similarly, in the case of cosmetics, Organisations use various methods to promote their sales like advertisements on traditional media like Television, Billboards, newspapers, magazines etc and also on Social media platform like Youtube, Instagram etc with the help of Celebrity Endorsers. The aim of the Research paper is to find out effectiveness of Celebrity Endorsement as a Marketing Tool and to Study the usage of Celebrity endorsement in Cosmetics Industry.